Implementasi Algoritma C4.5 Untuk Klasifikasi Tingkat Kepuasan Pembeli Online Shop - Febriyanto, Dimas Bayu; Handoko, Lovi; Wahyuli, Wahyuli; Aisyah, Hanif; Rumini, Rumini (STMIK Budi Darma, 2018)
This study applies the C4.5 algorithm in deciding customer satisfaction. The type of this research is classification with the concept of data mining by involving as many as 100 data which then take a sample of 15 data consumers of Vector Polaroid & Gift Jogja categorized by satisfied and dissatisfied. The method used in this research is classification method Classification is the process of finding a collection of patterns or functions that describe and separate data classes from one another, to be used, to predict data that does not yet have a particular data class. The results of the study have an accuracy rate of 91%, with the value of precision at predictive satisfaction of 66.67% and the value of precision in predictions not satisfied at 33.3%